Carbon nanotube dispersion
By using vinyl acetate/vinyl chloride copolymer and single-wall carbon nanotube dispersion technology in organic solvents, the problem of insufficient dispersion and stability in industrial applications is solved, and good conductivity and long-term stability are achieved.
Patent Information
- Application Number
- JP2023169785
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
The prior art has difficulty in effectively dispersing and stably dispersing single-walled carbon nanotubes (SWCNTs), resulting in insufficient conductivity and stability in industrial applications.
The organic solvent distribution containing single-walled carbon nanotubes and vinyl acetate/vinyl chloride copolymer is used. The content of vinyl acetate/vinyl chloride copolymer in this distribution is between 60 and 99%, vinyl acetate units are between 1-40%, and other vinyl units are between 0-20%, to ensure good dispersion and stability of carbon nanotubes.
It has achieved good dispersion and long-term stability of carbon nanotubes, and has good conductivity, making it suitable for various industrial applications, such as antistatic agents, conductive materials, plastic reformations, etc.
Smart Images

Figure 2025059601000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a dispersion of carbon nanotubes. The present invention relates to an organic solvent dispersion containing a tube and a vinyl chloride-fatty acid vinyl copolymer, and a product. [Background technology]
[0002] Carbon materials such as carbon black, graphite, and carbon nanotubes are known as industrial materials with excellent electrical conductivity. For example, attention has been paid to the electrical properties, thermal properties, and properties as a filler of carbon materials, and their use in antistatic agents, conductive materials, plastic reinforcing materials, semiconductors, fuel cell electrodes, display cathode rays, and the like has been considered. For these applications, a carbon material dispersion liquid is required in which the dispersibility of the carbon material is good and the dispersibility is maintained for a long period of time.
[0003] Carbon nanotubes, in particular, have excellent mechanical properties and thermal conductivity, and have been attracting attention in recent years as an industrial material. Carbon nanotubes include multi-walled carbon nanotubes (also known as MWCNTs (Multi Wall Carbon Nanotubes)) and single-walled carbon nanotubes (also known as SWCNTs (Single Wall Carbon Nanotubes)). Multi-walled carbon nanotubes were mass-produced and industrialized at an early stage. On the other hand, although there are high expectations for the functionality of single-walled carbon nanotubes, they have not yet been used to the same extent as multi-walled carbon nanotubes. This is because single-walled carbon nanotubes have the challenge of being more difficult to disperse and add.
[0004] In order to stably disperse carbon materials in liquid media, general dispersants are used. For example, Patent Documents 1 and 2 propose a solvent-based dispersion of carbon nanotubes using a cationic surfactant such as an alkanolamine salt or a polymer dispersant such as a styrene-acrylic resin. Patent Documents 3 and 4 propose dispersing carbon nanotubes in water using carboxymethyl cellulose or a salt thereof. Patent Document 5 proposes a conductive paste using a polyvinyl alcohol resin as a dispersing resin. Patent Documents 6 and 7 disclose a dispersion containing carbon nanotubes, a resin, a solvent, and the like, but there is room for improvement in terms of dispersibility. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2010-174084 A [Patent Document 2] Special Publication No. 2013-537570 [Patent Document 3] JP 2016-028109 A [Patent Document 4] JP 2016-204203 A [Patent Document 5] Patent Publication No. 2021-002520 [Patent Document 6] JP 2019-189857 A [Patent Document 7] JP 2023-004883 A Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, an object of the present invention is to provide a carbon nanotube dispersion that has excellent dispersibility of carbon nanotubes, has good stability over time, and is capable of exhibiting desired conductive performance. [Means for solving the problem]
[0007] As a result of extensive research into achieving the above-mentioned object, the inventors discovered that an organic solvent dispersion containing carbon nanotubes and vinyl chloride-fatty acid vinyl copolymer has excellent dispersibility of carbon nanotubes, good stability over time, and can exhibit the desired conductive performance, which led to the creation of the present invention.
[0008] That is, the present invention provides the following carbon nanotube dispersion. [1] (I) carbon nanotubes, (II) Vinyl chloride-fatty acid vinyl copolymer, and (III) Organic solvents A carbon nanotube dispersion comprising: [2] (I) 0.01 to 10% by mass of carbon nanotubes in a dispersion; (II) A vinyl chloride-fatty acid vinyl copolymer is dispersed in a dispersion at 0.01 to 30% by mass, and (III) The organic solvent is present in an amount of 40 to 99.89% by mass in the dispersion. The dispersion according to [1], [3] moreover, (IV) A dispersant other than component (II) is contained in an amount of 0.01 to 20% by mass in the dispersion. The dispersion according to [2], [4] (II) Vinyl chloride-fatty acid vinyl copolymer (A) 60 to 99 mass% vinyl chloride units, (B) 1 to 40% by mass of a fatty acid vinyl unit, and (C) 0 to 20% by mass of vinyl units other than the above (A) units and (B) units (The total of (A), (B) and (C) units is 100% by mass.) The dispersion according to any one of [1] to [3], comprising: [5] (III) The dispersion according to any one of [1] to [4], wherein the organic solvent is at least one selected from alcohols, ethylene glycols, glycol ethers, glycol ether acetates, propylene glycols, propylene glycol ethers, propylene glycol ether acetates, ethers, ketones, hydrocarbons, esters, and amide compounds. Effect of the Invention
[0009] The carbon nanotube dispersion of the present invention has excellent dispersibility of carbon nanotubes, good stability over time, and can exhibit desired conductive performance. The carbon nanotube dispersion of the present invention can be widely used in various applications such as antistatic agents, conductive materials, plastic reinforcing materials, semiconductors, fuel cell electrodes, and cathode rays for displays, focusing on the electrical properties, thermal properties, and properties as a filler. [Brief description of the drawings]
[0010] [Figure 1] 1 is a photograph showing the appearance of a coating film prepared from each dispersion of Example 18 and Comparative Example 1. [Diagram 2] 1 is an optical microscope photograph of a coating made from the dispersion of Example 8. [Diagram 3] 1 is an optical microscope photograph of a coating made from the dispersion of Example 9. [Figure 4] 1 is an optical microscope photograph of a coating made from the dispersion of Example 12. [Diagram 5] 1 is an optical microscope photograph of a coating made from the dispersion of Example 13. [Figure 6] 1 is an optical microscope photograph of a coating film made from the dispersion of Comparative Example 1. [Figure 7] 1 is an optical microscope photograph of a coating film made from the dispersion of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The carbon nanotube dispersion of the present invention contains (I) carbon nanotubes, (II) a vinyl chloride-fatty acid vinyl copolymer, (III) an organic solvent, and (IV) (if necessary) a dispersing agent other than component (II).
[0012] (I) Carbon nanotubes Carbon nanotubes (CNTs) are a type of carbon nanomaterial having a structure in which a graphene sheet is rolled into a cylindrical shape. Carbon nanotubes can be broadly divided into single-walled carbon nanotubes in which a single layer of graphene sheet is rolled into a cylindrical shape, and multi-walled carbon nanotubes in which multiple graphene sheets are rolled into a coaxial cylindrical shape. The carbon nanotubes (I) used in the present invention are not particularly limited to single-walled carbon nanotubes, multi-walled carbon nanotubes, etc., but are preferably single-walled carbon nanotubes. The outer diameter of single-walled carbon nanotubes is usually about 2.0 nm, and the outer diameter of multi-walled carbon nanotubes is usually several nm to 100 nm. The carbon nanotubes (I) used in the present invention preferably have an average outer diameter of 0.1 to 10 nm. The average outer diameter of carbon nanotubes is the average outer diameter measured by ultraviolet-visible-near infrared spectroscopy. The carbon nanotubes may be surface-treated carbon nanotubes. The carbon nanotubes may also be carbon nanotube derivatives to which a functional group, typically a carboxyl group, has been added. Carbon nanotubes containing organic compounds, metal atoms, or substances such as fullerenes can also be used.
[0013] The volume resistivity of carbon nanotubes is 1.0×10 -3 Ω cm~3.0×10 -2 Ω cm is preferred, and 1.0×10 -3 Ω cm~1.0×10 -2 It is more preferable that the volume resistivity is Ω·cm. The volume resistivity of the carbon nanotubes can be measured using a powder resistivity measuring device (Loresta GP Powder Resistivity Measuring System MCP-PD-51, manufactured by Mitsubishi Chemical Analytech Co., Ltd.).
[0014] The carbon purity of the carbon nanotube is expressed as the content (mass%) of carbon atoms in the carbon nanotube. The carbon purity is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more, relative to 100 mass% of the carbon nanotube.
[0015] The amount of metal contained in the carbon nanotube is preferably less than 20% by mass, more preferably less than 10% by mass, and even more preferably less than 5% by mass, based on 100% by mass of the carbon nanotube. Examples of metals contained in the carbon nanotube include metals and metal oxides used as catalysts when synthesizing carbon nanotubes. Specific examples include metals such as cobalt, nickel, aluminum, magnesium, silica, manganese, and molybdenum, metal oxides, and composite oxides thereof.
[0016] The carbon nanotubes may be pulverized carbon nanotubes. The pulverization is performed by using a pulverizer containing pulverization media such as beads or steel balls to pulverize the carbon nanotubes without the presence of any liquid material, and is also called dry pulverization. The pulverization is performed by utilizing the pulverization force or destructive force caused by the collision of pulverization media. The pulverization mainly has the effect of reducing the fiber length of the carbon nanotubes, and can improve the dispersibility of the carbon nanotubes. As a dry pulverization device, a known method such as a dry attritor, ball mill, vibration mill, or bead mill can be used, and the pulverization time can be set arbitrarily depending on the device.
[0017] The carbon nanotubes may be produced by any method, and are generally produced by, but not limited to, a laser ablation method, an arc discharge method, a thermal CVD method, a plasma CVD method, and a combustion method.
[0018] In the dispersion of the present invention, the blending amount of (I) carbon nanotubes varies depending on the application and is not particularly limited, but is preferably 0.01 to 10 mass% in the dispersion. From the viewpoint of dispersibility, it is more preferable that the blending amount of (I) carbon nanotubes in the dispersion is 0.01 to 1 mass%.
[0019] (II) Vinyl chloride-fatty acid vinyl copolymer The vinyl chloride-fatty acid vinyl copolymer (II) used in the present invention is preferably one comprising the following structural units (A) to (C): (A) 60 to 99 mass% vinyl chloride units, (B) 1 to 40% by mass of a fatty acid vinyl unit, and (C) 0 to 20% by mass of vinyl units other than the above (A) units and (B) units The sum of the (A), (B) and (C) units is 100% by mass.
[0020] The amount of the vinyl chloride-fatty acid vinyl copolymer (II) in the dispersion of the present invention varies depending on the application and is not particularly limited, but is preferably 0.01 to 30 mass % relative to the mass of the dispersion, and more preferably 0.1 to 20 mass %. If the amount of the copolymer (II) in the dispersion of the present invention is less than the lower limit, the carbon nanotubes may not be dispersed. If the amount of the copolymer (II) in the dispersion of the present invention is more than the upper limit, the conductivity of the carbon nanotubes may be impaired.
[0021] The vinyl chloride units (A) in the copolymer of component (II) are used to impart toughness and high surface hardness to the coating film. The constituent ratio of the vinyl chloride units in the copolymer of component (II) is preferably 60 to 99 mass%, more preferably 75 to 95 mass%. If the constituent ratio of the vinyl chloride units (A) in the copolymer of component (II) is less than the lower limit, the strength of the printing ink coating film may decrease, whereas if it exceeds the upper limit, the solubility in organic solvents may decrease, which may result in a decrease in dispersibility.
[0022] The proportion of the (B) fatty acid vinyl unit in the copolymer of component (II) is preferably 1 to 40 mass%, more preferably 1 to 25 mass%. If the proportion of the (B) fatty acid vinyl unit in the copolymer of component (II) is less than the lower limit, the solubility in organic solvents may decrease and the viscosity of the printing ink paint may increase, resulting in a decrease in dispersibility, while if it exceeds the upper limit, the strength and durability of the coating film may decrease. Examples of fatty acid vinyl include vinyl acetate, vinyl monochloroacetate, vinyl propionate, vinyl versatate, vinyl laurate, vinyl stearate, vinyl benzoate, etc., and vinyl acetate is preferred.
[0023] (C) Examples of vinyl units other than the above (A) units and (B) units include hydroxyl group-containing vinyl, epoxy group-containing vinyl, styrene, α-methylstyrene, acrylonitrile, alkyl (meth)acrylates such as methyl (meth)acrylate and ethyl (meth)acrylate, acrylic acid, methacrylic acid, maleic anhydride, crotonic acid, itaconic acid, and vinylidene chloride. The content of the (C) unit in the copolymer of component (II) is preferably 0 to 20% by mass, and if contained, is preferably 1 to 15% by mass. If the content of the (C) unit in the copolymer of component (II) exceeds the upper limit, the glass transition temperature decreases, and problems such as blocking may occur. Examples of the hydroxyl group-containing vinyl include hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polyethylene glycol polypropylene glycol mono(meth)acrylate, glycerol mono(meth)acrylate, glycerol monoallyl ether, hydroxyethyl vinyl ether, ethylene glycol monoallyl ether, hydroxybutyl vinyl ether, (meth)allyl alcohol, and N-methylol (meth)acrylamide, and hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate are preferred. Also, a part of the fatty acid vinyl may be saponified to form a vinyl alcohol unit.
[0024] The method for producing the vinyl chloride-fatty acid vinyl copolymer of component (II) is not particularly limited. For example, the above-mentioned vinyl chloride-fatty acid vinyl copolymer can be obtained by copolymerizing (a) 60-99% by mass of vinyl chloride monomer, (b) 1-40% by mass of fatty acid vinyl monomer, and (c) 0-20% by mass of vinyl monomer other than the above components (a) and (b). As described above, vinyl alcohol units can also be included by saponifying the fatty acid vinyl portion of the vinyl chloride-fatty acid vinyl copolymer.
[0025] In the copolymerization, the monomers of the components (a), (b) and (c) may be charged all at once before the start of polymerization, or may be polymerized separately into an initial charge before the start of polymerization and an additional charge. The vinyl chloride monomer (a) used as the raw material is preferably added during the copolymerization reaction, separately from the charge before the start of the copolymerization reaction, and the additional addition of the vinyl chloride monomer (a) is preferably carried out after the temperature is raised. It is preferable that the additional addition amount of the vinyl chloride monomer (a) used as the raw material is 40 to 80 mass %.
[0026] It is preferable to obtain the vinyl chloride-fatty acid vinyl copolymer by suspension polymerization. That is, after replacing the inside of a polymerization vessel with nitrogen, ion-exchanged water, a suspending agent, a polymerization initiator, (a) all or part of the vinyl chloride monomer, (b) all or part of the fatty acid vinyl monomer, and (c) all or part of the vinyl monomer other than the above are pressurized and the reaction is started by raising the temperature to the reaction temperature (polymerization temperature) under a nitrogen atmosphere, and the remaining (a) vinyl chloride monomer, (b) fatty acid vinyl monomer, and (c) vinyl monomer other than the above are added within a predetermined time to carry out suspension polymerization.
[0027] A chain transfer agent can be used in the production of the vinyl chloride-fatty acid vinyl copolymer of component (II), and the chain transfer agent may be any commonly used agent. Examples of the chain transfer agent include halogenated hydrocarbons such as trichloroethylene and carbon tetrachloride, mercaptans such as 2-mercaptoethanol, octyl 3-mercaptopropionate and dodecyl mercaptan, aldehydes such as acetone and n-butyl aldehyde, and cyclic organic phosphorus compounds. These may be used alone or in combination of two or more. The amount of the chain transfer agent is 0.3 to 0.6% by mass, preferably 0.4 to 0.5% by mass, based on the total amount of the monomers (a), (b) and (c).
[0028] Examples of the suspending agent include polyvinyl alcohol; partially saponified polyvinyl acetate; cellulose derivatives such as methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, and hydroxyethyl cellulose; synthetic polymers such as polyvinylpyrrolidone, polyacrylamide, maleic acid-styrene copolymer, and maleic acid-methyl vinyl ether copolymer; natural polymers such as starch and gelatin; polyalkylene oxides such as polyethylene oxide and polypropylene oxide; and oxyethylene-oxypropylene block copolymers. The suspending agent is preferably a compound having a weight-average molecular weight of 50,000 to 5,000,000, and is preferably a polyalkylene oxide such as polyethylene oxide and polypropylene oxide having a weight-average molecular weight of 50,000 to 1,000,000. The amount of the suspending agent is preferably 0.05 to 0.3% by mass based on the total amount of the monomers (a), (b), and (c). The above suspending agents may be used alone or in combination of two or more kinds.
[0029] Examples of the polymerization initiator include organic peroxides such as benzoyl peroxide, lauroyl peroxide, 3,3,5-trimethylhexanol peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, diethoxyethyl peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, butyl peroxyneodecanate, and di-3,5,5-trimethylhexanol peroxide; and azo compounds such as azobisisobutyronitrile and 2,2-azobis(2,4-dimethyl)valeronitrile. The polymerization initiator may be one of these alone or two or more of them in combination. The amount of the polymerization initiator is preferably 0.1 to 0.3% by mass based on the total amount of the monomers (a), (b), and (c).
[0030] The amount of ion-exchanged water used as a polymerization medium is preferably 50 to 200% by mass based on the total amount of monomers. Water-soluble alcohol such as methanol or isopropyl alcohol can be used in combination within a range not exceeding 50% by mass based on the total amount of monomers.
[0031] The polymerization temperature is preferably from 50 to 80°C, more preferably from 55 to 75°C.
[0032] In the polymerization, the above-mentioned chain transfer agent, polymerization initiator, suspending agent, etc. may be added to the polymerization system all at once at the start of the polymerization, or may be added in portions during the polymerization.
[0033] The vinyl chloride-fatty acid vinyl copolymer obtained by the above-mentioned suspension polymerization is then preferably separated from the aqueous medium and dried. The average particle size of the obtained dry powder of the vinyl chloride-fatty acid vinyl copolymer is preferably 50 to 500 μm. In this specification, the average particle size of the vinyl chloride-fatty acid vinyl copolymer is the particle size D at 50% of the cumulative particle size distribution on a volume basis, measured by a laser diffraction / scattering method. 50 (median diameter).
[0034] The average degree of polymerization of the vinyl units in the vinyl chloride-fatty acid vinyl copolymer is 150 to 750, and more preferably 200 to 500. The average degree of polymerization is the average degree of polymerization of the vinyl units obtained by dissolving a sample in nitrobenzene, measuring the time required for the sample to fall using an Ubbelohde viscometer in an atmosphere of 30.0°C, and converting the time into the number of seconds.
[0035] The weight average molecular weight of the vinyl chloride-fatty acid vinyl copolymer is preferably 20,000 or more, more preferably 25,000 or more. There is no particular upper limit, but it is preferably 150,000 or less. The weight average molecular weight is a value measured using a molecular weight distribution analyzer, for example, "GPC-900" manufactured by JASCO Corporation.
[0036] The glass transition temperature Tg of the vinyl chloride-fatty acid vinyl copolymer is preferably 50 to 90° C. The glass transition temperature Tg is the value of the inflection point of a baseline shift observed in a second heating curve obtained by measuring about 20 mg of the vinyl chloride-fatty acid vinyl copolymer powdered by spray drying at a heating rate of 5 K / min using a Shimadzu DSC (differential scanning calorimeter).
[0037] As described above, the vinyl chloride-fatty acid vinyl copolymer may be saponified using an alkali alcoholate in the presence of an organic solvent to convert a part of the fatty acid vinyl into vinyl alcohol units. The amount of the organic solvent used is preferably 100 to 300 parts by mass, and more preferably 150 to 250 parts by mass, per 100 parts by mass of the vinyl chloride-fatty acid vinyl copolymer. The saponification reaction temperature is preferably 25 to 60°C, and more preferably 30 to 55°C. The saponification reaction time is preferably 3 to 5 hours.
[0038] (III) Organic solvents (III) The organic solvent may be any solvent capable of dispersing carbon nanotubes well and dissolving the vinyl chloride-fatty acid vinyl copolymer. When the dispersion of the present invention is used as, for example, a coating composition, the organic solvent has a function of increasing affinity for a substrate.The organic solvent is not particularly limited, and examples thereof include alcohols such as methanol, ethanol, 2-propanol, 1-propanol, trimethylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, catechol, cyclohexanediol, cyclohexanedimethanol, and glycerin; ethylene glycols such as ethylene glycol, diethylene glycol, triethylene glycol, and tetraethylene glycol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, ethylene glycol diethyl ether, and diethylene glycol dimethyl ether; glycol ether acetates such as ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate; propylene glycols such as propylene glycol, dipropylene glycol, and tripropylene glycol; propylene glycol monomethyl ether propylene glycol ethers such as propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, propylene glycol dimethyl ether, and propylene glycol diethyl ether; propylene glycol ether acetates such as propylene glycol monomethyl ether acetate; ethers such as diethyl ether, diisopropyl ether, methyl-t-butyl ether, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, isophorone, and acetylacetone; hydrocarbons such as toluene, xylene (o-, m-, or p-xylene), hexane, and heptane; esters such as ethyl acetate, butyl acetate, ethyl acetoacetate, methyl orthoacetate, ethyl orthoformate, and propylene carbonate; amide compounds such as N-methylformamide, N,N-dimethylformamide, and N-methylpyrrolidone; compounds having a sulfo group such as dimethyl sulfoxide; compounds having a cyano group such as acetonitrile; and halogens.The organic solvent may be one type alone, a mixed solvent of two or more types of the above-mentioned organic solvents, or a mixed solvent of the above-mentioned organic solvents with water (a water-containing organic solvent).
[0039] In order to improve the coatability, it is also effective to add the above-mentioned ethylene glycols, propylene glycols, amide compounds, etc.
[0040] The amount of the organic solvent is, for example, preferably from 40 to 99.98 mass %, more preferably from 50 to 99.98 mass %, and even more preferably from 60 to 99.98 mass %, based on the mass of the entire dispersion.
[0041] (IV) Dispersants other than component (II) In addition, the dispersion of the present invention may contain a dispersant other than the component (II) for the purpose of facilitating wetting and dispersion stabilization of carbon nanotubes. The dispersant other than the component (II) is not particularly limited as long as it can disperse carbon nanotubes, particularly single-walled carbon nanotubes, in a medium. The component (IV) may be, for example, a low molecular weight compound or a polymeric compound having a polar group such as a nitrogen-containing group, a sulfur-containing group, an oxygen-containing group, or a phosphorus-containing group. In the case of a polymeric compound, the molecular structure may be any of a linear polymer, a graft polymer, a dendrimer, and a hyperbranched polymer. Specific examples of the component (IV) include amine compounds having 6 to 18 carbon atoms such as octylamine, hexylamine, and oleylamine; sulfur compounds having 6 to 18 carbon atoms such as dodecanethiol; carboxylic acid compounds having 6 to 18 carbon atoms such as oleic acid; various polymeric compounds such as polyvinyl alcohol and polyvinyl butyral (butyral resin); various phosphoric acid esters; surfactants such as sodium dodecyl sulfate and sodium dodecylbenzene sulfate; and cellulose derivatives such as carboxymethyl cellulose or a salt thereof. These may be used alone or in combination of two or more. The dispersant other than the component (II) is preferably blended in an amount of 0 to 20 mass % in the dispersion, more preferably 0.01 to 20 mass %, and even more preferably 0.01 to 10 mass %.
[0042] Method for producing the dispersion The dispersion of the present invention is prepared to a concentration and hardness suited to the intended use and process so that it can be dispersed simultaneously in the manufacturing equipment of the target material, and there are no limitations on the manufacturing method thereof.
[0043] Dispersion methods for dispersion bodies have been reported in many documents, and there are many methods recommended by dispersing machine manufacturers, but in the preparation of the dispersion body of the present invention, any dispersion method that can reach a bundle state may be used. Examples of dispersion devices include high-speed agitators, homogenizers, planetary mixers, planetary mixers, self-rotating mixers, roll mills, wet mills, colloid mills, bead mills, attritors, ball mills, ultrasonic dispersers, high-pressure dispersers, static mixers, kneaders, Banbury mixers, extruders, etc.
[0044] The ideal dispersion of carbon nanotubes is when they are bundled in the target composition and form a network structure connected by three-dimensional interactions. This extremely fine three-dimensional carbon network structure improves electrical conductivity and strength. In addition, it has a secondary effect of imparting unique rheological properties by assuming a state similar to a dilute physical gel, and the uniform dispersion of thin fibers with adsorption and cohesion improves correlation adhesion. The dispersion of the present invention has excellent dispersibility and good stability over time, and can exhibit the desired conductive performance. The dispersibility and stability over time of the dispersion are confirmed by visually checking the fluidity and the presence or absence of gelation, and the changes over time, and by comparing the changes in TDNMR, light transmittance, and viscosity.
[0045] Considering printing applications, the viscosity of the dispersion of the present invention is, for example, in the range of 0.1 Pa·s to 30 Pa·s, preferably 5 Pa·s to 25 Pa·s, under environmental temperature conditions during printing (e.g., 25°C). If the viscosity of the dispersion is below the lower limit, the fluidity of the dispersion is too high, which may cause problems in the reception of the dispersion (ink) from the intaglio to the blanket, or in the transfer of the ink from the blanket to the substrate to be printed. On the other hand, if the viscosity of the dispersion exceeds the upper limit, the fluidity of the dispersion is too low, which may cause poor filling of the recesses of the intaglio. If the filling of the recesses is poor, the accuracy of the pattern transferred to the substrate is reduced, causing problems such as breakage of thin lines.
[0046] The dispersion of the present invention can be applied onto a substrate by known methods such as spin coating, (doctor) knife coating, microgravure coating, direct gravure coating, offset gravure, reverse gravure, reverse roll coating, (Mayer) bar coating, die coating, spray coating, and dip coating.
[0047] The thickness of the coating film formed by applying the dispersion of the present invention to a substrate may be appropriately set depending on the purpose, but from the standpoint of cost and performance, it is preferably 0.01 to 200 μm, and more preferably 0.3 to 100 μm.
[0048] The dispersion of the present invention has a conductive film with a sheet resistance of 1.0x10 2 ~1.0x10 14 Ω / sq, and further characterized by 1.0x10 3 ~1.0x10 9 It is preferably Ω / sq.
[0049] The dispersion of the present invention can be used as a coating composition for antistatic, electrostatic dispersion, conductivity, EMI shielding or electrodes. By forming a substrate having a film formed with the dispersion, antistatic materials, electrostatic dispersions, conductive films, electromagnetic wave shielding materials, electromagnetic wave absorbing materials, solar cells, electrodes for dye-sensitized solar cells (DSSC), electric and electronic elements, positive and negative electrode active materials for secondary batteries and electrochemical elements using the same, secondary batteries, fuel cells, solar cells, memory elements, electrochemical elements such as hybrid capacitors (P-EDLC) or capacitors, semiconductor elements, photoelectric elements, notebook computer parts, computer parts, mobile phone parts, PDA parts, PSP parts, game console parts, housings, transparent electrodes, opaque electrodes, field emission displays (FEDs), back light units (BLUs), liquid crystal displays (LCDs), plasma display panels (PDPs), luminescent diodes (LEDs), and other devices can be manufactured. It can be used in electronic devices such as electronic components, electronic equipment, electronic devices, electronic equipment ... EXAMPLES
[0050] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, "parts" refers to "parts by mass".
[0051] In the following, the constituent units of the copolymer were identified using a near-infrared analyzer (NIRFlex N-500, manufactured by Nippon Buchi Co., Ltd.). In the following, the methods for measuring the various physical properties of the copolymer are as follows. The average degree of polymerization was calculated from the results of measuring the time required for a sample of the copolymer dissolved in nitrobenzene to fall at 30.0° C. using an Ubbelohde viscometer. The weight average molecular weight was measured using a molecular weight distribution analyzer GPC-900 (manufactured by JASCO Corporation). The glass transition temperature (Tg) was measured for about 20 mg of the copolymer using a DSC (differential scanning calorimeter, manufactured by Shimadzu Corporation) at a heating rate of 5 K / min. The average particle size was measured using a laser diffraction / scattering type particle size distribution measuring device LA-950V2 (manufactured by HORIBA Corporation).
[0052] [Production Example I-1] Single-walled carbon nanotube dispersion A single-walled carbon nanotube (CNT) dispersion was obtained by mixing and dispersing 0.4 parts of single-walled carbon nanotubes (TUBALL 01RW02 manufactured by OSiAl, average outer diameter 1.6 nm), 1.0 parts of butyral resin (S-LEC manufactured by Sekisui Chemical) as a dispersant, and 98.6 parts of propylene glycol monomethyl ether acetate (PGMEA) as a solvent.
[0053] [Manufacturing example II-1] Into an autoclave equipped with a stirrer, 1200 parts of deionized water, 1200 parts of methanol, 2 parts of hydroxypropyl methylcellulose, 3 parts of dibenzoyl peroxide, and 1 part of di(3,5,5-trimerylhexanoyl) peroxide were charged. After nitrogen replacement, 580 parts of vinyl chloride monomer and 390 parts of vinyl acetate monomer were charged into the autoclave and stirred. The mixture was then heated to 74°C while stirring under a nitrogen gas atmosphere, and immediately after the temperature reached 74°C, 1000 parts of vinyl chloride monomer was continuously injected over 7 hours to allow the copolymerization reaction to proceed. When the internal pressure of the autoclave reached 0.22 MPa, the polymerization was terminated, and post-treatment (degassing, deliquation, and drying) was carried out to obtain a white powder. Next, 1365 parts of methanol, 385 parts of acetone, and 20 parts of sodium hydroxide were stirred and dissolved in a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and then 1000 parts of the obtained white powder was added and stirred. Then, the temperature was raised to 35°C while stirring, and the saponification reaction was started. The reaction was terminated 3 hours after the start of the reaction, and post-treatment (washing, deliquation, and drying) was performed to obtain a copolymer. The obtained product was a copolymer having 91.5% by mass of vinyl chloride-derived units, 3.0% by mass of vinyl acetate-derived units, and 5.5% by mass of hydroxyl-containing vinyl (vinyl alcohol)-derived units. The average degree of polymerization, weight-average molecular weight, glass transition temperature (Tg), and average particle size of the obtained copolymer were measured by the above-mentioned methods. The results are shown in Table 1.
[0054] [Manufacturing example II-2] Into an autoclave equipped with a stirrer, 1150 parts of deionized water, 1000 parts of methanol, 2 parts of hydroxypropylmethylcellulose, 3 parts of dibenzoyl peroxide, and 1 part of dilauroyl peroxide were charged. After nitrogen replacement, 1150 parts of vinyl chloride monomer and 560 parts of vinyl acetate monomer were charged into the autoclave and stirred. The mixture was then heated to 74°C under a nitrogen gas atmosphere while stirring, and immediately after the temperature reached 74°C, 1330 parts of vinyl chloride monomer was continuously injected over 7 hours to allow the copolymerization reaction to proceed. When the internal pressure of the autoclave reached 0.22 MPa, the polymerization was terminated, and post-treatment (degassing, deliquation, and drying) was carried out to obtain a white powder. Next, 10,800 parts of methanol, 320 parts of acetone, and 32 parts of sodium hydroxide were stirred and dissolved in a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and then 1,000 parts of the obtained white powder and 12 parts of N,N-dimethylaminoethanol were added and stirred. The temperature was then raised to 50°C while stirring, and the saponification reaction was initiated. The reaction was terminated 8 hours after the start of the reaction, and post-treatment (washing, deliquation, and drying) was performed to obtain a copolymer. The obtained product was a copolymer having 91.0% by mass of vinyl chloride-derived units, 2.0% by mass of vinyl acetate-derived units, and 7.0% by mass of hydroxyl-containing vinyl (vinyl alcohol)-derived units. The average degree of polymerization, weight-average molecular weight, glass transition temperature (Tg), and average particle size of the obtained copolymer were measured by the above-mentioned methods. The results are shown in Table 1.
[0055] [Manufacturing example II-3] Into an autoclave equipped with a stirrer, 1200 parts of deionized water, 1200 parts of methanol, 2 parts of hydroxypropyl methylcellulose, 3 parts of dibenzoyl peroxide, and 1 part of di(3,5,5-trimerylhexanoyl) peroxide were charged. After nitrogen replacement, 580 parts of vinyl chloride monomer and 390 parts of vinyl acetate monomer were charged into the autoclave and stirred. The mixture was then heated to 74°C while stirring under a nitrogen gas atmosphere, and immediately after the temperature reached 74°C, 1000 parts of vinyl chloride monomer was continuously injected over 7 hours to allow the copolymerization reaction to proceed. When the internal pressure of the autoclave reached 0.22 MPa, the polymerization was terminated, and post-treatment (degassing, deliquation, and drying) was carried out to obtain a white powder. The obtained product was a copolymer having 87.0% by mass of vinyl chloride-derived units and 13.0% by mass of vinyl acetate-derived units. The average degree of polymerization, weight average molecular weight, glass transition temperature (Tg), and average particle size of the obtained copolymer were measured by the above-mentioned methods. The results are shown in Table 1.
[0056] [Manufacturing example II-4] Into an autoclave equipped with a stirrer, 1030 parts of deionized water, 1030 parts of methanol, 1 part of hydroxypropyl methylcellulose, 9 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 5 parts of di(3,5,5-trimerylhexanoyl)peroxide, and 1 part of t-butyl peroxypivalate were charged. After nitrogen replacement, 644 parts of vinyl chloride monomer and 100 parts of vinyl acetate monomer were charged into the autoclave and stirred. Thereafter, the temperature was raised to 63°C while stirring under a nitrogen gas atmosphere, and immediately after reaching 63°C, 970 parts of vinyl chloride monomer and 315 parts of hydroxyalkyl acrylate were continuously injected over 7 hours to allow the copolymerization reaction to proceed. When the pressure inside the autoclave reached 0.22 MPa, the polymerization was terminated, and post-treatment (degassing, deliquation, and drying) was performed to obtain a white powder. The obtained product was a copolymer having 83.0% by mass of vinyl chloride-derived units, 4.0% by mass of vinyl acetate-derived units, and 13.0% by mass of hydroxyl-containing vinyl (hydroxyalkyl acrylate)-derived units. The average degree of polymerization, weight-average molecular weight, glass transition temperature (Tg), and average particle size of the obtained copolymer were measured by the above-mentioned methods. The results are shown in Table 1.
[0057] [Table 1] The other vinyl units in Production Examples II-1 and II-2 are vinyl alcohol units obtained by subjecting a portion of vinyl acetate to a saponification reaction.
[0058] [Example 1] 0.3 parts of the copolymer of Production Example II-1 was added to 29.7 parts of diethylene glycol monobutyl ether acetate (BDGAc, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Furthermore, 5.4 parts of the single-walled carbon nanotube dispersion of Production Example I-1 and 0.6 parts of the copolymer solution were mixed together to obtain a carbon nanotube dispersion.
[0059] [Example 2] A sample was prepared in the same manner as in Example 1. The change was that 4.2 parts of the single-walled carbon nanotube dispersion of Production Example I-1 and 1.8 parts of the copolymer solution of Example 1 were added and mixed to obtain a carbon nanotube organic solvent dispersion.
[0060] [Example 3] A sample was prepared in the same manner as in Example 1. The only change was that 3.0 parts of the single-walled carbon nanotube dispersion of Production Example I-1 and 3.0 parts of the copolymer solution of Example 1 were added and mixed to obtain a carbon nanotube dispersion.
[0061] [Example 4] 0.3 parts of the copolymer of Production Example II-2 was added to 29.7 parts of diethylene glycol monobutyl ether acetate (BDGAc, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were added and mixed to obtain a carbon nanotube dispersion.
[0062] [Example 5] A sample was prepared in the same manner as in Example 1. The only change was that 1.2 parts of the single-walled carbon nanotube dispersion of Production Example I-1 and 4.8 parts of the copolymer solution of Example 1 were added and mixed to obtain a carbon nanotube dispersion.
[0063] [Example 6] 0.3 parts of the copolymer of Production Example II-1 was added to 29.7 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved by stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0064] [Example 7] 1.5 parts of the copolymer of Production Example II-1 was added to 28.5 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0065] [Example 8] 3.0 parts of the copolymer of Production Example II-1 was added to 27.0 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0066] [Example 9] 6.0 parts of the copolymer of Production Example II-1 was added to 24.0 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0067] [Example 10] 0.3 parts of the copolymer of Production Example II-2 was added to 29.7 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved by stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0068] [Example 11] 1.5 parts of the copolymer of Production Example II-2 was added to 28.5 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved by stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0069] [Example 12] 3.0 parts of the copolymer of Production Example II-2 was added to 27.0 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0070] [Example 13] 6.0 parts of the copolymer of Production Example II-2 was added to 24.0 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0071] [Example 14] 1.5 parts of the copolymer of Production Example II-3 was added to 28.5 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved by stirring to obtain a copolymer solution. Furthermore, 3.0 parts of the single-walled carbon nanotube dispersion of Production Example I-1 and 3.0 parts of the copolymer solution were mixed together to obtain a carbon nanotube organic solvent dispersion.
[0072] [Example 15] 1.5 parts of the copolymer of Production Example II-4 was added to 28.5 parts of propylene glycol monomethyl ether acetate (PGMEA, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved by stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0073] [Example 16] 0.3 parts of the copolymer of Production Example II-1 was added to 29.7 parts of N-methyl-2-pyrrolidone (NMP, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0074] [Example 17] 1.5 parts of the copolymer of Production Example II-1 was added to 28.5 parts of N-methyl-2-pyrrolidone (NMP, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0075] [Example 18] 3.0 parts of the copolymer of Production Example II-1 was added to 27.0 parts of N-methyl-2-pyrrolidone (NMP, Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved with stirring to obtain a copolymer solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the copolymer solution were mixed to obtain a carbon nanotube dispersion.
[0076] [Comparative Example 1] The single-walled carbon nanotube dispersion obtained in Production Example I-1 was used.
[0077] [Comparative Example 2] A carbon nanotube dispersion was obtained by mixing 3.0 parts of the single-walled carbon nanotube dispersion obtained in Production Example I-1 and 3.0 parts of propylene glycol monomethyl ether acetate (PGMEA, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0078] [Comparative Example 3] 5.0 parts of polyurethane resin solution (TA24-537Q: manufactured by Resonac, polyurethane resin: 30%, ethyl acetate, 2-propanol mixture: 70%) was added to 25.0 parts of propylene glycol monomethyl ether acetate (PGMEA, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved by stirring to obtain a polyurethane resin solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the polyurethane resin solution were mixed together to obtain a carbon nanotube dispersion.
[0079] [Comparative Example 4] 10.0 parts of a polyurethane resin solution (TA24-537Q: manufactured by Resonac) was added to 20.0 parts of propylene glycol monomethyl ether acetate (PGMEA, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and dissolved by stirring to obtain a polyurethane resin solution. Further, 3.0 parts of the single-walled carbon nanotube dispersion liquid of Production Example I-1 and 3.0 parts of the polyurethane resin solution were mixed together to obtain a carbon nanotube dispersion.
[0080] ·Dispersibility The state of the dispersion immediately after preparation was visually confirmed. 〇: Fluid and carbon nanotubes are dispersed △: Poor fluidity and gelation ×: No fluidity at all, sedimentation
[0081] ·Dispersion stability The state of the dispersion was visually confirmed 3 days after the preparation of the dispersion. 〇: Fluid and carbon nanotubes are dispersed △: Poor fluidity and gelation ×: No fluidity at all, sedimentation
[0082] Coating properties The condition of the coating film when the dispersion was applied with the applicator was visually confirmed. Figure 1A shows a photograph of the appearance of the coating film produced from the dispersion of Comparative Example 1, and Figure 1B shows a photograph of the appearance of the coating film produced from the dispersion of Example 18. Furthermore, optical microscope photographs of the coating films produced from each of the dispersions of Examples 8, 9, 12, and 13 and each of the dispersions of Comparative Examples 1 and 2 are shown in Figures 2 to 7. 〇: The coating is evenly applied. △: The coating film has some unevenness. ×: The coating film cannot be applied.
[0083] Conductive In the resistance value evaluation below, the cases where the surface resistance value could be measured were marked with an ◯, and the cases where the surface resistance value could not be measured were marked with an X.
[0084] Resistance value The dispersion was applied onto a PET film using a 4 mil applicator (101.6 μm). It was then dried in a dryer at 130° C. for 30 minutes to obtain a coating film. The thickness of the resulting coating film is determined by the solid content of (I) and (II). The resistance value of the coating film (film thickness after drying: 0.4 to 12 μm) was measured using an applicator of 4 mil with an insulation resistance meter PDM5219S (manufactured by Sanwa Electric Instruments Co., Ltd.). The lower the surface resistance value (Ω / sq), the higher the conductivity. When the carbon nanotube concentration is 0.2 wt%, the surface resistance value is particularly preferably 1.0×10 9 Less than Ω / sq is good.
[0085] [Table 2]
[0086] [Table 3]
[0087] [Table 4]
[0088]
Table 5
Claims
1. (I) carbon nanotubes, (II) vinyl chloride / fatty acid vinyl copolymer, and (III) Organic solvent A carbon nanotube dispersion comprising:
2. (I) 0.01 to 10% by mass of carbon nanotubes in the dispersion; (II) a vinyl chloride / fatty acid vinyl copolymer in a dispersion of 0.01 to 30% by mass, and (III) The organic solvent is present in an amount of 40 to 99.98% by mass in the dispersion. The dispersion of claim 1 comprising:
3. moreover, (IV) A dispersant other than the component (II) is contained in the dispersion in an amount of 0.01 to 20% by mass. The dispersion of claim 2 comprising
4. (II) The vinyl chloride / fatty acid vinyl copolymer is (A) 60 to 99% by mass of vinyl chloride units, (B) 1 to 40% by mass of a fatty acid vinyl unit, and (C) Vinyl units other than the above (A) units and (B) units: 0 to 20% by mass (The total of (A), (B) and (C) units is 100% by mass.) The dispersion of claim 1 comprising:
5. (III) The dispersion according to any one of claims 1 to 4, wherein the organic solvent is at least one selected from the group consisting of alcohols, ethylene glycols, glycol ethers, glycol ether acetates, propylene glycols, propylene glycol ethers, propylene glycol ether acetates, ethers, ketones, hydrocarbons, esters, and amide compounds.
Citation Information
Patent Citations
Anti static resin plate, and transfer sheet for manufacturing anti static resin couple
JP2009090611A
Antistatic resin molding and its manufacturing method
JP2009178957A
Antistatic resin molding
JP2009220565A
Thermoelectric conversion material-containing resin composition, and film formed by thermoelectric conversion material-containing resin composition
JP2015170766A
Carbon nanotube dispersion and utilization of the same
WO2009098779A1